Antimicrobial Potential Of Endophyte Bacteria In Angsana Plants (Pterocarpus indicus Willd) - Nurhasnah Nurhasnah; Media Roza; Milya Sari; Kencanawati Kencanawati (Bioscience, 2024)
The discovery of antimicrobial active compounds is one of the pressing things in the world of medicine and the pharmaceutical industry, due to the increasing and widespread resistance of pathogenic bacteria to existing antimicrobials. Angsana plant (Pterocarpus Indicus Willd) has been shown to have efficacy as a drug, so it has the potential to be used as a source of natural antibiotics. This study aims to find out the types of endophytes in various parts of the Angsana plant (Pterocarpus indicus Willd) through macroscopic and microscopic identification and find out the activity of antimicrobial compound-producing endophye bacteria in Angsana plants. Bacterial purification techniques use streak plate and spread plate methods. Antimicrobial activity tests are carried out using diffusion methods by means of point inoculation. The results showed 29 isolates of endophye bacteria isolated from the Angsana plant (Pterocarpus indicus Willd). From the roots as many as 11 isolates, stems as many as 12 isolates, and leaves as many as 6 isolates. The result of Gram staining of Angsana plant endophyte bacteria, obtained 22 bacterial isolates including Gram positive and 7 is Gram negative. There were 21 bacil-shaped endophyte bacterial isolates, 7 coccus-shaped isolates and 1 coccobacil-shaped isolate. Isolate the endophyte bacteria of Angsana plants that have the potential to produce antimicrobial compounds as many as 20 isolates. Isolates of Angsana plant endophyte bacteria form a bland zone in    S. aureus (10 isolates), E. coli (17 isolates). Endophyte bacterial isolates that are able to inhibit the growth of bacteria S. aureus and  E. coli are 7 isolates